The implementation of "at least 30% of women in decision making policy" in Malaysia public sector: women empowerment and quality of life analysis / Norfarhanis Mahamad Sukri - Mahamad Sukri, Norfarhanis (2015)
Women in Malaysia have gone through many phases of development and the participation of women in labor force is vital for the economic development. There are many policies, institutions and international commitment such as National Policy of Women (1989)(2009); Ministry of Women, Family and Community Development (2001) are introduced in order to ensure women's advancement and empowerment. However, although there are many opportunities given, women in Malaysia are facing many challenges due to the work life balance issues, cultural and religious expectation that believe women are not eligible to hold high positions. Hence, the objectives of this study are; to determine the relationship between women empowerment and quality of life (subjective wellbeing) and to analyse whether the 'at least 30% of women in decision making' policy is empowering women decision makers and improves their quality of life after 8 years of its introduction in 2004. Furthermore, this study will adopt Sara Longwe's women empowerment framework that comprises five dimensions which are welfare, access, conscientisation, participation, and control as indicators for women empowerment. Consequently, the scope of this study is women respondents in the six selected ministries which are Ministry of Health, Ministry of Finance, Ministry of Higher Learning Education, Ministry of Education, Ministry of Rural and Regional Development and Prime Minister Department. The methodology employed for this research is crosssectional with convenience sampling technique for the identification of the units of analysis - women in the middle decision making positions. Through a list provided by Human Resource Department of Public Service Department Malaysia, this research targeting five hundred women that holding grade 41-54 positions were sent questionnaires for data collection. Prior to the actual data collection, a pilot study was undertaken to ensure the reliability and validity of the instrument. Subsequently, the study found that the welfare (r=0.147, p<0.05), access (r=0.379, p<0.05), conscientisation (r=0.251, p=<0.005), participation (r=0.357, p<0.05) and control (r=0.226, p<0.05) were significantly correlated with the quality of life (subjective wellbeing) and access was the most influential factor towards the quality of life (subjective wellbeing) which indicates (~=0.256, p<0.05). In addition, the findings also showed that the 30% policy was moderates the relationship between women empowerment and quality of life (subjective wellbeing) when the value ofR square increased from .252 to .283. This finding indicates the 30% policy does facilitate women empowerment process towards achieving quality of life (subjective wellbeing.